Basis sets applied to the theoretical study of the vibrational structure of hexaaquaaluminum(III) ion - Treu, O.; Pinheiro, J. C.; Kondo, R. T. (Elsevier B.V., 2004)
Gaussian basis sets were developed with the Generator Coordinate Hartree-Fock (GCHF) method for the atoms from H (14s), O (23s16p), and Al (29sl9p) in the ground state. These basis sets were then contracted to 3s (12,1,1), 5s3p (18,2,1,1,1/14,1,1), and 7s5p (20,3,2,1,1,1,1/14,2,1,1,1) for H, O and Al atoms, respectively, by a standard procedure. The quality of contracted basis sets in molecular calculations was evaluated through studies of the total and orbital (epsilon(HOMO) and epsilon(HOMO-1)) energies at the HF level for the hexaaquaaluminum(III) ion, [AI(H(2)O)(6)](3+). For the O atom, the 5s3p was supplemented with d polarization function and it was used in combination with 3s, and 7s5p for H and Al atoms was used to the theoretical interpretation of the Infrared (IR) spectrum of hexaaquaaluminum(III) ion. The calculations of the IR-spectrum were also performed at the HF level and it showed that the basis sets obtained with the aid of GCHF method lead to the selection of useful contracted Gaussian basis sets for the theoretical study of vibrational property of ionic specie of our interest. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Gaussian basis sets; CGHF method; theoretical study; vibrational structure; hexaaquaaluminum(III) ion